The NCAN gene: schizophrenia susceptibility and cognitive dysfunction - Wang P; Cai J; Ni J; Zhang J; Tang W; Zhang C (Neuropsychiatric Disease and Treatment)
Peirong Wang,1 Jun Cai,2 Jianliang Ni,1 Jiangtao Zhang,1 Wei Tang,3 Chen Zhang2 1Department of Psychiatry, Tongde Hospital of Zhejiang Province, Hangzhou, Zhejiang, 2Schizophrenia Program, Shanghai Mental Health Center, Shanghai Jiao Tong University School of Medicine, Shanghai, 3Wenzhou Kangning Hospital, Wenzhou, Zhejiang, People’s Republic of China Background: Cognitive dysfunction has been recognized as a cardinal feature of schizophrenia. Elucidating the neurobiological substrates of cognitive dysfunction in schizophrenia would help identify the underlying mechanism of this disorder. The rs1064395 single nucleotide polymorphism, within the gene encoding neurocan (NCAN), is reported to be associated with schizophrenia in European populations and may influence brain structure in patients with schizophrenia.Methods: In this study, we aimed to explore whether NCAN rs1064395 confers some risk for schizophrenia and cognitive dysfunction in Han Chinese. We recruited 681 patients with schizophrenia and 699 healthy subjects. Two hundred and fifty-four patients were evaluated according to Repeatable Battery for the Assessment of Neuropsychological Status (RBANS).Results: There were no significant differences in genotype or allele distributions of the rs1064395 polymorphism between the schizophrenia and control groups. Patients showed significantly poorer performance than controls on immediate memory, visuospatial skill, language, attention, delayed memory, and total RBANS score. Patients with the A/A or A/G genotype of rs1064395 had lower scores of immediate memory, visuospatial skill, attention, and total RBANS score than those with the G/G genotype. We performed an expression quantitative trait loci analysis and observed a significant association between rs1064395 and NCAN expression in the frontal (P=0.0022, P=0.022 after Bonferroni correction) and cerebellar cortex (P=0.0032, P=0.032 after Bonferroni correction).Conclusion: Our findings indicate that this single nucleotide polymorphism may be a risk factor for cognitive dysfunction in patients with schizophrenia. Further investigations are warranted for validation purposes and to identify the precise mechanism by which rs1064395 influences cognitive performance in patients with schizophrenia. Keywords: NCAN, schizophrenia, cognitive function, polymorphism, eQTL